Cooling effect on electrode and process parameters in EDM - Abdulkareem, Suleiman; Khan, Ahsan Ali; Konneh, Mohamed (Taylor & Francis, 2010)
In electrical discharge machining (EDM), material is removed by a series of electrical sparks that develops a temperature in the range 8,000'C–12,000'C between the electrode and the workpiece. Due to the high temperature of the sparks, the workpiece is melted and vaporized. At the same time, the electrode material is also eroded by melting and vaporization. This erosion of the electrode is termed as electrode wear (EW). The EW process is similar to the material removal mechanism as the electrode and the workpiece are considered as a set of electrodes in EDM. Due to EW, electrodes lose their dimensions resulting in inaccuracy of the cavity formed by EDM. This paper reports on the study of the effect of electrode cooling during the EDM of titanium alloy (Ti-6Al-4V). Investigation on the effect of electrode cooling on electrode wear was carried out. Current, pulse on-time, pause off-time, and gap voltage were considered as the machining parameters while EW is the response. Analysis of the influence of electrode cooling on the response has been carried out, and it was possible to reduce EW by 27% using this method.